2021
DOI: 10.3389/fonc.2021.777617
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in the Mechanism Research and Clinical Treatment of Anti-Angiogenesis in Biliary Tract Cancer

Abstract: Biliary tract cancers (BTCs), including cholangiocarcinoma (CCA) and gallbladder cancer (GC), are malignancies originating from the biliary tract with poor prognosis. In the early stage of BTCs, surgery is the only choice for cure. Unfortunately, most patients with BTC are diagnosed at an advanced stage and lose the opportunity for surgery. For many advanced solid tumors, antiangiogenic therapy has achieved encouraging results. While most clinical studies on antiangiogenic therapy in advanced BTCs have shown a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 121 publications
(128 reference statements)
0
10
0
Order By: Relevance
“…Different studies have demonstrated that MVD is a hallmark of tumor neovascularization, and higher MVD is associated with an advanced tumor stage and low cure and high recurrence rates after surgical resection. Several signal cascades, including those regulated by VEGF, Platelet-derived growth factor (PDGF), and FGFR, play a crucial role in the pathogenesis and progression of BTCs [ 44 ]. Specifically, VEGF overexpression is observed in 42–76% of patients with unresectable advanced BTC and is associated with poor prognosis [ 14 , 45 ].…”
Section: Angiogenesis As a Hallmark Of Btcsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different studies have demonstrated that MVD is a hallmark of tumor neovascularization, and higher MVD is associated with an advanced tumor stage and low cure and high recurrence rates after surgical resection. Several signal cascades, including those regulated by VEGF, Platelet-derived growth factor (PDGF), and FGFR, play a crucial role in the pathogenesis and progression of BTCs [ 44 ]. Specifically, VEGF overexpression is observed in 42–76% of patients with unresectable advanced BTC and is associated with poor prognosis [ 14 , 45 ].…”
Section: Angiogenesis As a Hallmark Of Btcsmentioning
confidence: 99%
“…Furthermore, FGFR plays an important role in the regulation of cell proliferation, migration, invasion, and angiogenesis in BTC. Previous studies have identified FGFR fusions in patients with BTC and have shown that the presence of these alterations predicts a more favorable prognosis [ 44 ]. Several clinical trials of drugs targeting FGFR fusions, including Infigratinib, Pemigatinib, and Derazantinib, have been conducted [ 58 ].…”
Section: Angiogenesis As a Hallmark Of Btcsmentioning
confidence: 99%
“…Angiogenesis plays a crucial role in the development of ESCC, by delivering oxygen and nutrients to tumors, and its key mediator is VEGF ( 138 ). Distant vascular metastasis is another way of tumor progression.…”
Section: Targeting Tumor Microenvironment For Esophageal Squamous Cel...mentioning
confidence: 99%
“…CCA, a type of bile duct cancer, is classified into two main subtypes based on its anatomical location: intrahepatic CCA (iCCA) and extrahepatic CCA (eCCA). The eCCA subtype can be further divided into perihilar CCA (pCCA) and distal CCA (dCCA) based on its specific location within the bile ducts 4–6 . CCA differs from other malignant hepatobiliary tumours as CCA contains more genomics variations 7 .…”
Section: Introductionmentioning
confidence: 99%
“…KRAS, TP53, IDH1/2 and ARID1A are the most common mutated genes in iCCA 8 while KRAS, TP53, ARID1A and SMAD4 are the most common mutated genes in eCCA 9 . despite the presence of numerous actionable genomic alterations in CCA, only a limited number of established treatment regimens are available for this disease 5,7 . For advanced CCA, the first‐line treatment is gemcitabine‐based chemotherapy, while for patients with FGFR fusion mutation, the optional treatment scheme includes pemigatinib and infigratinib 10–12 .…”
Section: Introductionmentioning
confidence: 99%